How to Boost the Development of the Russian Economy: Priority Actions (Suggestions for the Main Activities of the State until 2024) - V. V. Ivanter; V. N. Porfiryev; D. E. Sorokin; M. A. Eskindarov; V. V. Maslennikov; A. A. Shirov; N. M. Abdikeev; M. A. Abramova; Yu. S. Bogachev; L. I. Goncharenko; O. Dzh. Govtvan’; M. S. Gusev; et al. (Финансы: теория и практика, 2018)
This report was prepared by the staff of the Institute for Economic Forecast of the Russian Academy of Sciences and the Financial University under the Government of the Russian Federation. It gives suggestions to implement priority measures to facilitate the transfer the Russian economy to the direction defined by the Decree of the President of the Russian Federation (est. May 7, 2018). The report also highlights priority directions of the economic policy, primarily in investment activity, development of the domestic market, as well as financial and organizational support for the suggested actions.